Is nitric oxide an essential mediator in cervical inflammation and preterm birth?. (3rd July 2018) - Nold, Christopher; Stone, Julie; Graham, Maura; Trinh, Jennifer; Blanchette, Alex; Jensen, Todd
Abstract: Objective: Cervical ripening is an obligatory step in the process of preterm birth. We hypothesize an inflammatory challenge to the cervix, which leads to an increase in nitric oxide production, disrupting the cervical epithelial barrier leading to preterm birth. Study design: For this study, three experiments were performed: (i) Using a mouse model, pregnant mice were treated with an intrauterine injection of saline or lipopolysaccharide (LPS). Mice were sacrificed and cervices were collected for molecular analysis. (ii) Immortalized ectocervical and endocervical cells were treated with either LPS or the nitric oxide donor sodium nitroprusside (SNP). Media and RNA was collected for analysis. (iii) The integrity of the epithelial cell barrier was evaluated using an in vitro permeability assay. Results: The expression of inducible nitric oxide synthase (iNOS) was increased in our mouse model with LPS ( p  < .005). In vitro, LPS did not increase nitrate or nitrite concentrations or mRNA expression of iNOS. Permeability increased in the presence of LPS ( p  < .01), but was unchanged after treatment with SNP. Conclusions: These studies show that LPS increases the expression of the iNOS in an animal model of preterm birth, but the nitric oxide metabolites nitrate and nitrite do not initiate the pro-inflammatory LPS-induced breakdown of the cervical epithelial barrier.